Intermediate Band Characteristics of Defective Perovskite Cs2SnI6 in Comparison with CsSnI3: Insights into Its Role as Hole Transport Material for Solar Cells - Handayani, Yolla Sukma; Sukmawati, Sri; Nurunnizar, Adhita Asma (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2026)
Tin-based halide perovskites have recently attracted attention as promising alternatives to toxic lead-based perovskites for solar cell applications. This study aims to investigate the electronic and optical properties of cesium tin hexaiodide (Cs2SnI6) and to elucidate its functional role in perovskite solar cells, particularly in determining whether it is more suitable as a light absorber or as a hole transport material (HTM). For comparison, the properties of cesium tin tri-iodide (CsSnI₃) are also systematically analyzed using Density Functional Theory (DFT) calculations within the Perdew-Burke-Ernzerhof (PBE) functional and Heyd-Scuseria-Ernzerhof 2006 (HSE06) hybrid functional frameworks. While previous theoretical studies have predominantly examined these materials separately, a comprehensive understanding of the role of defect-induced intermediate bands in Cs2snI6 remains limited. The results reveal that CsSnI₃ exhibits a direct band gap, while Cs₂SnI₆ shows an intermediate band (IB) located between the valence band maximum (VBM) and conduction band minimum (CBM). The calculated band gap of Cs₂SnI₆ is 0.28 eV using PBE and 0.82 eV using HSE06, confirming the role of Sn(5s) and I(5p) states in the IB formation. Furthermore, optical property calculations further demonstrate that Cs₂SnI₆ exhibits a relatively high dielectric constant and distinct absorption features associated with interband transitions, although with lower absorption intensity compared to CsSnI₃. These findings suggest that CsSnI₃ is suitable as a light absorber, whereas Cs₂SnI₆ is more favorable as an HTM in perovskite solar cell architectures. Overall, this work offers new insights into the functional role of Cs₂SnI₆ and its potential contribution for efficient lead-free perovskite solar cells.